Cashew Nut Meal as a Feed Ingredient for Livestock – A Review - Kavitha, R.; Gayathri, J. (Indian Journal of Animal Nutrition, 2025)
India, the world’s largest producer of milk, faces significant challenges in meeting the growing demand for milk production while ensuring affordable and adequate nutrition for dairy cattle. Traditional protein sources, such as soybean meal and groundnut cake, have seen rising costs, prompting the exploration of alternative, cost-effective feed ingredients for cattle feed. Cashew Nut Meal (CNM), a byproduct of cashew nut processing, presents a promising alternative due to its favorable nutritional profile and potential economic benefits. This review aims to explore the feasibility of utilizing CNM as a protein source in livestock diets, focusing on its nutritional value, economic viability, and challenges associated with its use. The paper discusses the role of agricultural by-products in enhancing livestock nutrition and promoting sustainable farming practices. Future research is recommended to focus on comprehensive nutritional profiling of CNM, the mitigation of anti nutritional factors, and the development of innovative processing methods to improve its bioavailability. Additionally, establishing quality control standards and conducting life cycle assessments can ensure the sustainability of CNM as a feed ingredient. The support of CNM effectively, livestock producers, especially in cashew-growing regions, can reduce feed costs, improve feed efficiency, and contribute to more sustainable and profitable dairy farming practices.